APPROPRIATION IN INTERACTIVE ART - KHAIRUN NISA, BINTI SOHAIMI (Universiti Malaysia Sarawak(UNIMAS), 2019)
This research is done in order to understand ppropriation in art, to explore interactive in art and to create an interactive artwork by using appropriation technique. Thus, this research is entitled ‘Appropriation in Interactive’ art. Researcher collect the data for this research through online survey, observation, journals, books and websites. Throughout the research, researcher can concludes interactive art as a form of art that will requires audience participation. Meanwhile, appropriation in art is the act of using everyday object or existing artwork into a new artwork to give it a new meaning. After being able to understand interactive art and appropriation in art, researcher then create an interactive artwork by appropriating digital game technique into it. The artwork entitled ‘For You’ and with that, researcher hope people’s perspective towards fine art will change.